2021
DOI: 10.52547/sjku.26.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficiency of general hospitals in Iran

Abstract: Background and aim: Approximately 85% of Iranian hospitals are general hospitals. Considering the limitation of resourses, improvement of the hospital efficiency is an absolute necessity. Efficiency, as the output-input ratio, indicates use of the lowest amount of inputs to produce the greatest amount of outputs. The aim of this study was to determine the efficiency of general hospitals in Iran and identification of the factors affecting efficiency of the hospitals. Materials and Methods:In this cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Husseini et al ranked factors affecting the productivity of the human resource of the Doroud Cement Factory by ANP technique (15) and found that the results were incompatible with those of this study. In addition, the results of some other studies, including Luturlean et al ( 16), Mosadeghrad et al (17), and Kiani and Radfard (13), were consistent with those of this study but did not match with those of Ali et al (4).…”
Section: Discussionsupporting
confidence: 78%
“…Husseini et al ranked factors affecting the productivity of the human resource of the Doroud Cement Factory by ANP technique (15) and found that the results were incompatible with those of this study. In addition, the results of some other studies, including Luturlean et al ( 16), Mosadeghrad et al (17), and Kiani and Radfard (13), were consistent with those of this study but did not match with those of Ali et al (4).…”
Section: Discussionsupporting
confidence: 78%
“…It is highly centralized and almost all of the decisions about general goals, policies and allocation of resources for an extensive healthcare network that offers basic healthcare services in addition to public health programmes, such as primary, secondary and tertiary health care, and medical education are made at the national level by the Ministry of Health and Medical Education (MOHME) in the Iranian government (Azizi, 2007). The ministry consists of nine deputies as follows: deputy for food and drugs; deputy for research and technology; deputy for health; deputy for education; deputy for culture and students’ affairs; deputy for treatment; deputy for legal, parliamentary and provincial affairs; deputy for management development, resources and planning; and deputy for nursing (Mosadeghrad & Rahimi‐Tab ar, 2019). Yet, the ministry delegates its responsibilities to over 60 affiliated universities of medical sciences and health services across the country.…”
Section: Introductionmentioning
confidence: 99%
“…Iran’s health system is organised at three levels: country, province and city 28 as well as public, private and Non-governmental organizations. 29 The Ministry of Health and Medical Education is responsible for planning, monitoring, and supervising health-related activities in Iran’s public and private sectors.…”
Section: Methodsmentioning
confidence: 99%